Oncologic emergencies: a review - Baruah, Minoti (International Journal of Research in Medical Sciences, 2018)
Cancer and its treatment include many medical emergencies. Hence taking care of these emergencies presents a challenge not only to the clinicians but also to the medical oncologists. Cancer patients may have complex medical problems in addition to cancer such as coronary heart diseases, diabetes mellitus, and respiratory diseases. Such patients require immediate medical assistance and emergency care facilities to improvise their health condition. The present review paper focuses on more commonly confronted emergencies in cancer patients and their related management.